A secure authentication scheme for bluetooth connection - Diallo, Alhassane Saliou; Wajdi, Al Khateeb; Olanrewaju, Rashidah Funke; Sado, Fatai (2014)
Recently, Bluetooth technology is widely used by organizations and individuals to provide wireless personal area network (WPAN) because the radio frequency (RF) waves can easily penetrate obstacles and can propagate without direct line-of-sight (LoS).